A prospect theory application to understand tourism in terror infested destinations. (10th April 2019) - Pandey, Shivendra Kumar
Rational consumers avoid travel destinations with terrorism associated but a set of customers go despite the risk. The current study used prospect theory as plausible explanations of such irrational behaviours by using domestic and international tourist arrivals to a terror-infested destination. Multiple regressions with independents such as terror and peace yielded exciting results. Terror events affect tourist arrivals, but peace was not significant. No long-term effect of terrorism on tourism was found in the ten-year study period. Both domestic and international tourist arrivals showed high growth with adequate prediction and less variability. Prospect theory tenets of loss aversion and relative change found support whereas isolation effect was not supported. Implications for tourism managers and media managers are highlighted.